2016
DOI: 10.4183/aeb.2016.130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on miR-29 and IGF-1 Expression and Lipid Profile in the Heart of Ovariectomized Rat

Abstract: introduction. Menopause increases the risk of cardiovascular disease in women. The aims of the present study were to evaluate the effects of swimming training on cardiac histology and expression of miR-29 and IGF-1 in the ovariectomized rats. materials and methods. Thirty female Wistar rats were divided into sham and ovariectomized groups: sedentary control (OVX) and trained with 8 weeks exercise (OVX.E). On 57 th day, blood was collected and used for lipid profile measurement. In addition, heart tissue was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Cell apoptosis is well understood to play an important role in tissue homeostasis, such as in muscle myoblasts. As a negative regulator of myoblast apoptosis, miR-29 can affect the growth of rat myocardium by inhibiting IGF1 expression, 43 as well as inhibit proliferation and promote both apoptosis and differentiation of murine embryonic cardiomyocytes. 44 Herein, the co-transfection of goat primary myoblasts with si-circUSP13 and miR-29c inhibitor demonstrated that circUSP13 functions as a ceRNA of miR-29c regulating myoblast development.…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis is well understood to play an important role in tissue homeostasis, such as in muscle myoblasts. As a negative regulator of myoblast apoptosis, miR-29 can affect the growth of rat myocardium by inhibiting IGF1 expression, 43 as well as inhibit proliferation and promote both apoptosis and differentiation of murine embryonic cardiomyocytes. 44 Herein, the co-transfection of goat primary myoblasts with si-circUSP13 and miR-29c inhibitor demonstrated that circUSP13 functions as a ceRNA of miR-29c regulating myoblast development.…”
Section: Discussionmentioning
confidence: 99%
“…Habibi et al . [46] recently reported the up-regulation of microRNA-29 with swimming training in OVX rats and suggested that swimming exercise training protectively regulates the heart against fibrosis by targeting the IGF-1 signalling pathway. These findings, combined with numerous reports on microRNA-29 gene as a fibrosis suppressor [15, 47], suggest that exercise training plays an important role in the development of cardiac fibrosis under pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The oviduct and each ovary were sectioned and separated. Then, a silk thread sutured the skin and muscle walls (24,25).…”
Section: Ovariectomy Surgerymentioning
confidence: 99%